Anti-blue light polaroid and production process thereof
By using composite anti -blue light and specific process steps in polarizing tablets, the existing polarizer has the problem of poor anti -blue light performance, and achieves high -efficiency and long -term anti -blue light effects, suitable for electronic display and other scenarios.
Patent Information
- Application Number
- CN202411734238.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polarizers have poor blue light resistance and cannot maintain their high performance for a long time, making it difficult to meet consumers' demand for high-quality visual protection.
Adopt anti -Blu -ray polarizers made of PVA membrane, anti -blue light composite solution, TAC membrane, pressure -sensitive glue, protective membrane, and deolved membrane, and prepare composite anti -blue light agents through specific process steps to enhance the combination of layers and Anti -blue light effect.
A significant anti -blue light effect can be achieved, which can effectively absorb and block blue light, reduce the damage of blue light to the eyes, enhance the viewing experience, and have long -term stability, maintain high anti -blue light effect and apply to various electronic display.
Smart Images

Figure CN119376005A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polarizers, and in particular to an anti-blue light polarizer and a production process thereof. Background Art
[0002] Polarizers, as an important optical material, are widely used in the field of electronic device displays. With the continuous development of science and technology, people are exposed to more and more electronic devices in their daily lives, such as mobile phones, computers, and tablets. The blue light emitted by these electronic devices is potentially harmful to the human eye. When exposed to blue light of a certain intensity and duration, it will seriously affect the function of retinal cells and even cause death, thereby causing related diseases such as macular degeneration and retinitis pigmentosa. Therefore, in today's information age, it is imperative to prevent harmful blue light and protect the eyes.
[0003] However, currently, common polarizers can only slightly or even fail to filter some blue light, resulting in poor anti-blue light performance and inability to maintain high performance for a long time, making it difficult to meet consumers' demand for high-quality visual protection. Therefore, it is of great practical significance to develop an anti-blue light polarizer and its production process.
[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide an anti-blue light polarizer and its production process, which solves the problem that the existing polarizer has poor anti-blue light performance and cannot maintain its high performance for a long time, making it difficult to meet consumers' demand for high-quality visual protection.
[0006] The purpose of the present invention can be achieved by the following technical solutions: An anti-blue light polarizer is composited by a PVA film, an anti-blue light composite liquid, a TAC film, a pressure-sensitive adhesive, a protective film and a release film; The anti-blue light composite liquid includes the following components in parts by weight: 10-15 parts of carrier resin, 0.5-2.5 parts of composite anti-blue light agent and 40-45 parts of ethyl acetate; Wherein, the composite anti-blue light agent is prepared by the following steps: Step a1: 2-(tributyltin)thiophene, tetrakis(triphenylphosphine)palladium and toluene are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred and reacted for 15-25 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, diethyl 2,5-dibromoterephthalate is added and the stirring reaction is continued for 15-25 minutes. Then, the mixture is heated to 100-105° C. and the stirring reaction is continued for 6-8 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. Then, the mixture is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 2-3 hours to obtain intermediate 1; Step a2: Add intermediate 1, N-bromosuccinimide and tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then heat to 50-55°C and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then pour it into a saturated sodium thiosulfate solution, and then extract it with dichloromethane 2-3 times, combine the extracts and rotary evaporate them to remove the solvent, and then recrystallize with a mixed solvent to obtain intermediate 2; Step a3: Add intermediate 2, 2,4-dihydroxybenzophenone, triethylamine and tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, then heat to 70-75°C and continue stirring and reacting for 5-6 hours. After the reaction is completed, cool the reaction product to room temperature, then pour it into ice water, and then vacuum filter it. Wash the filter cake with a saturated sodium bicarbonate solution for 2-3 times, then place it in a vacuum drying oven, dry it at a temperature of 50-55°C for 2-3 hours, and then recrystallize it with anhydrous ethanol to obtain intermediate 3; Step a4: Add intermediate 3, sodium hydroxide and anhydrous ethanol to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a reflux condenser, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then raise the temperature to reflux and continue stirring the reaction for 6-8h. After the reaction is completed, cool the reaction product to room temperature, then pour it into distilled water, and then extract it with dichloromethane 2-3 times, combine the extracts and rotary evaporate them to remove the solvent to obtain intermediate 4; Step a5: Add intermediate 4, 3-aminopropyltrimethoxysilane, p-toluenesulfonic acid, toluene and N,N-dimethylacetamide to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then heat to reflux and continue stirring the reaction for 3-5h. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent to obtain an anti-blue light enhancer; Step a6: Add zinc acetate, cadmium chloride, lithium hydroxide and anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 50-55°C and continue stirring and reacting for 1-2 hours. After the reaction is completed, cool the reaction product to room temperature, pour it into n-hexane, let it stand overnight, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 60-65°C for 1-2 hours. Then place it in a muffle furnace and calcine it at a temperature of 300-350°C for 2-3 hours, and then cool it with the furnace to obtain a nano anti-blue light agent; Step a7: Add the nano anti-blue light agent, anhydrous ethanol and deionized water to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adjust the pH to 9-10 with ammonia water, then add the anti-blue light enhancer and continue stirring and reacting for 20-30 minutes, then heat to 80-85°C and continue stirring and reacting for 2-3 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with methanol 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 3-5 hours to obtain a composite anti-blue light agent.
[0007] As a preferred embodiment of the present invention, the usage ratio of the 2-(tributyltin)thiophene, tetrakis(triphenylphosphine)palladium, toluene and diethyl 2,5-dibromoterephthalate in step a1 is 22-25mmol:0.3-0.7g:70-80mL:10mmol.
[0008] As a preferred embodiment of the present invention, the usage ratio of the intermediate 1, N-bromosuccinimide and tetrahydrofuran in step a2 is 10mmol:22-25mmol:60-70mL; the mixed solvent is a mixture of ethyl acetate and petroleum ether in a volume ratio of 1:8-10.
[0009] As a preferred embodiment of the present invention, the usage ratio of the intermediate 2, 2,4-dihydroxybenzophenone, triethylamine and tetrahydrofuran in step a3 is 10 mmol: 20 mmol: 25-30 mmol: 60-80 mL.
[0010] As a preferred embodiment of the present invention, the usage ratio of the intermediate 3, sodium hydroxide and anhydrous ethanol in step a4 is 10 mmol: 40-50 mmol: 60-80 mL.
[0011] As a preferred embodiment of the present invention, the usage ratio of the intermediate 4, 3-aminopropyltrimethoxysilane, p-toluenesulfonic acid, toluene and N,N-dimethylacetamide in step a5 is 10mmol:20mmol:0.1-0.2g:20-25mL:60-70mL.
[0012] As a preferred embodiment of the present invention, the usage ratio of the zinc acetate, cadmium chloride, lithium hydroxide and anhydrous ethanol in step a6 is 2g:0.02-0.04g:0.2-0.3g:50-60mL.
[0013] As a preferred embodiment of the present invention, the dosage ratio of the nano anti-blue light agent, anhydrous ethanol, deionized water and anti-blue light enhancer in step a7 is 10g:60-70mL:60-70mL:0.7-2.1g; the mass fraction of the ammonia water is 20-25%.
[0014] As a preferred embodiment of the present invention, a production process of an anti-blue light polarizer comprises the following steps: Step 1: Weigh 10-15 parts of carrier resin, 0.5-2.5 parts of composite anti-blue light agent and 40-45 parts of ethyl acetate according to weight, and set aside; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step 2: Evenly mix the carrier resin, the composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step 3: coating the anti-blue light composite liquid on both sides of the PVA film, and compounding the TAC film on both sides to obtain a composite base film; Step 4: Coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film respectively, then composite a protective film on the other side of the anti-blue light composite liquid, and composite a release film on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0015] As a preferred embodiment of the present invention, the thickness of the PVA film is 30-35μm; the coating thickness of the anti-blue light composite liquid is 15-17μm; the thickness of the TAC film is 75-80μm; the coating thickness of the pressure-sensitive adhesive is 25-28μm; the thickness of the protective film is 58-60μm; and the thickness of the release film is 38-40μm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: An anti-blue light polarizer and a production process thereof, comprising the steps of uniformly mixing a carrier resin, a composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid, coating the anti-blue light composite liquid on both sides of a PVA film and composite TAC films on both sides to obtain a composite base film, coating the anti-blue light composite liquid and a pressure-sensitive adhesive on both sides of the composite base film respectively, and then composite a protective film on the other side of the anti-blue light composite liquid and a release film on the other side of the pressure-sensitive adhesive to obtain the anti-blue light polarizer; the anti-blue light polarizer realizes bonding and composite action by using the anti-blue light composite liquid containing the composite anti-blue light agent, thereby improving the interlayer bonding force of the anti-blue light polarizer, improving its mechanical properties and durability, and making it have a significant anti-blue light effect, can effectively absorb and block blue light, reduce the damage of blue light to eyes, and enhance viewing experience, and at the same time, has long-term stability, so that it can maintain a high anti-blue light effect for a long time, can have stable working performance for a long time, so that it can maintain a good visual effect, is suitable for various electronic display screens and other scenes requiring anti-blue light protection, and has a simple and easy production process, low cost, and is suitable for large-scale production.
[0017] In the process of preparing the anti-blue light polarizer, a composite anti-blue light agent is first prepared. First, 2-(tributyltin)thiophene and diethyl 2,5-dibromoterephthalate are reacted. The tributyltin structure on 2-(tributyltin)thiophene reacts with the bromine atom on diethyl 2,5-dibromoterephthalate, thereby replacing the bromine atom on the thiophene ring to obtain intermediate 1. Then, intermediate 1 is reacted with N-bromosuccinimide, and N-bromosuccinimide is used as a brominating agent to introduce a bromine atom into the thiophene ring of intermediate 1. Then, intermediate 2 and 2,4-dibromoterephthalate are used to react. The bromine atom on the intermediate 2 reacts with the hydroxyl group on the 2,4-dihydroxybenzophenone to introduce the benzophenone structure to obtain the intermediate 3, and then the intermediate 3 is reacted with sodium hydroxide, and the ester group on the intermediate 3 forms a carboxyl group under the action of sodium hydroxide to obtain the intermediate 4, and then the intermediate 4 is reacted with 3-aminopropyltrimethoxysilane, and the carboxyl group on the intermediate 4 reacts with the amino group on the 3-aminopropyltrimethoxysilane to introduce a large amount of siloxane to obtain the anti-blue light enhancer, and then zinc acetate and cadmium chloride are used as raw materials to prepare the doped Cadmium-doped zinc oxide nanoparticles are used to obtain a nano anti-blue light agent, and finally the nano anti-blue light agent is treated with an anti-blue light enhancer. The siloxane groups on the anti-blue light enhancer are hydrolyzed to form silanes that can be grafted on the ionic surface of the nano anti-blue light agent to obtain a composite anti-blue light agent. Zinc oxide is a semiconductor material with unique electrical and optical properties. Its absorption region is in the ultraviolet light band, which gives the composite anti-blue light agent excellent anti-blue light performance. Doping with cadmium elements can adjust the bandgap width of the material to form a composite structure, thereby enhancing the photosensitization effect and making it anti-blue light. It can be further improved, and the composite anti-blue light agent is a composite structure of organic matter coated with inorganic matter, which has excellent dispersibility and can be evenly and stably distributed, so as to achieve the best anti-blue light performance. The introduced thiophene ring structure and benzophenone structure can absorb light of certain specific bands, further improving the blue light absorption effect of the composite anti-blue light agent, and also giving it excellent photo-oxidation and aging performance, so that the final composite anti-blue light agent has excellent anti-blue light performance and can maintain high performance for a long time, which can effectively improve the optical performance of the anti-blue light polarizer. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0019] Figure 1 It is a schematic structural diagram of the anti-blue light polarizer of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Embodiment 1: See also Figure 1 As shown, this embodiment is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: 22 mmol 2-(tributyltin)thiophene, 0.3 g tetrakis(triphenylphosphine)palladium and 70 mL toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred and reacted for 15 min at a temperature of 25° C. and a stirring rate of 300 r / min. Then, 10 mmol 2,5-dibromoterephthalate was added and the mixture was stirred and reacted for 15 min. Then, the mixture was heated to 100° C. and the mixture was stirred and reacted for 6 h. After the reaction, the reaction product was cooled to room temperature, and the solvent was removed by rotary evaporation. Then, the mixture was washed with distilled water twice, and then placed in a vacuum drying oven and dried at 50° C. for 2 h to obtain intermediate 1. Step S2: 10 mmol of intermediate 1, 22 mmol of N-bromosuccinimide and 60 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at a temperature of -5°C and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 50°C and continued to stir for 2 h. After the reaction, the reaction product was cooled to room temperature, and then poured into a saturated sodium thiosulfate solution, and then extracted twice with dichloromethane, the extracts were combined and rotary evaporated to remove the solvent, and then recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:8 to obtain intermediate 2; Step S3: 10 mmol of intermediate 2, 20 mmol of 2,4-dihydroxybenzophenone, 25 mmol of triethylamine and 60 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of -5°C and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 70°C and stirred for 5 h. After the reaction, the reaction product was cooled to room temperature, poured into ice water, and then vacuum filtered. The filter cake was washed twice with a saturated sodium bicarbonate solution, and then placed in a vacuum drying oven, dried at a temperature of 50°C for 2 h, and then recrystallized from anhydrous ethanol to obtain intermediate 3; Step S4: 10 mmol of intermediate 3, 40 mmol of sodium hydroxide and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to reflux and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted twice with dichloromethane, the extracts were combined and the solvent was removed by rotary evaporation to obtain intermediate 4; Step S5: 10 mmol of intermediate 4, 20 mmol of 3-aminopropyltrimethoxysilane, 0.1 g of p-toluenesulfonic acid, 20 mL of toluene and 60 mL of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to reflux and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an anti-blue light enhancer; Step S6: Add 2g zinc acetate, 0.02g cadmium chloride, 0.2g lithium hydroxide and 50mL anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20min at a temperature of 25°C and a stirring rate of 300r / min, then heat to 50°C and continue stirring and reacting for 1h. After the reaction is completed, cool the reaction product to room temperature, pour it into n-hexane, let it stand overnight, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 60°C for 1h. Then place it in a muffle furnace and calcine it at a temperature of 300°C for 2h, and then cool it with the furnace to obtain a nano anti-blue light agent; Step S7: 10 g of nano anti-blue light agent, 60 mL of anhydrous ethanol and 60 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25°C and a stirring rate of 300 r / min for 20 min, and then adjusted to pH 9 with 20% ammonia water, and then added 0.7 g of anti-blue light enhancer and continued to stir for 20 min, and then heated to 80°C and continued to stir for 2 h. After the reaction, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with methanol, and then placed in a vacuum drying oven and dried at 50°C for 3 h to obtain a composite anti-blue light agent; Step S8: 10 parts of carrier resin, 0.5 parts of composite anti-blue light agent and 40 parts of ethyl acetate are weighed in parts by weight for later use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S9: uniformly mixing the carrier resin, the composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step S10: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S11: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0022] Embodiment 2: See also Figure 1 As shown, this embodiment is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: 24 mmol 2-(tributyltin)thiophene, 0.5 g tetrakis(triphenylphosphine)palladium and 75 mL toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred and reacted for 20 min at a temperature of 28° C. and a stirring rate of 350 r / min. Then, 10 mmol 2,5-dibromoterephthalate was added and the mixture was stirred and reacted for 20 min. Then, the mixture was heated to 100-102° C. and the mixture was stirred and reacted for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, the mixture was washed with distilled water twice, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 2.5 h to obtain intermediate 1. Step S2: 10 mmol of intermediate 1, 24 mmol of N-bromosuccinimide and 65 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at a temperature of -3°C and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 52°C and continued to stir for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into a saturated sodium thiosulfate solution, and then extracted twice with dichloromethane, the extracts were combined and rotary evaporated to remove the solvent, and then recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:9 to obtain intermediate 2; Step S3: 10 mmol of intermediate 2, 20 mmol of 2,4-dihydroxybenzophenone, 28 mmol of triethylamine and 70 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The reaction was stirred for 25 min at a temperature of -3 ° C and a stirring rate of 350 r / min, and then the temperature was raised to 72 ° C and the stirring reaction was continued for 5.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into ice water, and then vacuum filtered. The filter cake was washed twice with a saturated sodium bicarbonate solution, and then placed in a vacuum drying oven, dried at a temperature of 52 ° C for 2.5 h, and then recrystallized from anhydrous ethanol to obtain intermediate 3; Step S4: 10 mmol of intermediate 3, 45 mmol of sodium hydroxide and 70 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to reflux and continued to stir for 7 h. After the reaction, the reaction product was cooled to room temperature, poured into distilled water, and then extracted twice with dichloromethane. The extracts were combined and rotary evaporated to remove the solvent to obtain intermediate 4; Step S5: 10 mmol of intermediate 4, 20 mmol of 3-aminopropyltrimethoxysilane, 0.15 g of p-toluenesulfonic acid, 22 mL of toluene and 65 mL of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the temperature was raised to reflux and the stirring reaction was continued for 4 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an anti-blue light enhancer; Step S6: Add 2g zinc acetate, 0.03g cadmium chloride, 0.25g lithium hydroxide and 55mL anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 25min at a temperature of 28°C and a stirring rate of 350r / min, then heat to 52°C and continue stirring and reacting for 1.5h. After the reaction is completed, cool the reaction product to room temperature, pour it into n-hexane, let it stand overnight, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 62°C for 1.5h. Then place it in a muffle furnace and calcine it at a temperature of 325°C for 2.5h, and then cool it with the furnace to obtain a nano anti-blue light agent; Step S7: 10 g of nano anti-blue light agent, 65 mL of anhydrous ethanol and 65 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the pH was adjusted to 9.5 with 22% ammonia water by mass, and then 1.4 g of anti-blue light enhancer was added and the mixture was stirred for reaction for 25 min, and then the mixture was heated to 82° C. and stirred for reaction for 2.5 h. After the reaction, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with methanol, and then placed in a vacuum drying oven and dried at 52° C. for 4 h to obtain a composite anti-blue light agent; Step S8: weigh 12 parts of carrier resin, 1.5 parts of composite anti-blue light agent and 42 parts of ethyl acetate according to weight parts for later use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S9: uniformly mixing the carrier resin, the composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step S10: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S11: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0023] Embodiment 3: See also Figure 1 As shown, this embodiment is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: 25 mmol 2-(tributyltin)thiophene, 0.7 g tetrakis(triphenylphosphine)palladium and 80 mL toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred and reacted for 25 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 10 mmol 2,5-dibromoterephthalate was added and the stirring reaction was continued for 25 min. Then, the mixture was heated to 105° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, the mixture was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 3 h to obtain intermediate 1. Step S2: 10 mmol of intermediate 1, 25 mmol of N-bromosuccinimide and 70 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 0° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 55° C. and continued to stir for 3 h. After the reaction, the reaction product was cooled to room temperature, and then poured into a saturated sodium thiosulfate solution, and then extracted with dichloromethane for 3 times. The extracts were combined and rotary evaporated to remove the solvent, and then recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:10 to obtain intermediate 2; Step S3: 10 mmol of intermediate 2, 20 mmol of 2,4-dihydroxybenzophenone, 30 mmol of triethylamine and 80 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 0°C and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 75°C and continued to stir for 6 h. After the reaction, the reaction product was cooled to room temperature, poured into ice water, and then vacuum filtered. The filter cake was washed 3 times with a saturated sodium bicarbonate solution, and then placed in a vacuum drying oven, dried at 55°C for 3 h, and then recrystallized from anhydrous ethanol to obtain intermediate 3; Step S4: 10 mmol of intermediate 3, 50 mmol of sodium hydroxide and 80 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted with dichloromethane for 3 times, the extracts were combined and rotary evaporated to remove the solvent, to obtain intermediate 4; Step S5: 10 mmol of intermediate 4, 20 mmol of 3-aminopropyltrimethoxysilane, 0.2 g of p-toluenesulfonic acid, 25 mL of toluene and 70 mL of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then the temperature was raised to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an anti-blue light enhancer; Step S6: Add 2g zinc acetate, 0.04g cadmium chloride, 0.3g lithium hydroxide and 60mL anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then heat to 55°C and continue stirring and reacting for 2h. After the reaction is completed, cool the reaction product to room temperature, pour it into n-hexane, let it stand overnight, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 65°C for 2h, then place it in a muffle furnace, calcine it at a temperature of 350°C for 3h, and then cool it with the furnace to obtain a nano anti-blue light agent; Step S7: 10 g of nano anti-blue light agent, 70 mL of anhydrous ethanol and 70 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and the mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the pH was adjusted to 10 with 25% ammonia water, and then 2.1 g of anti-blue light enhancer was added and the stirring reaction was continued for 30 min, and then the temperature was raised to 85° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with methanol 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain a composite anti-blue light agent; Step S8: weighing 15 parts of carrier resin, 2.5 parts of composite anti-blue light agent and 45 parts of ethyl acetate according to weight parts for standby use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S9: uniformly mixing the carrier resin, the composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step S10: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S11: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0024] Comparative Example 1: See also Figure 1 As shown, this comparative example is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: weigh 15 parts of carrier resin and 45 parts of ethyl acetate according to weight and set aside; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S2: uniformly mixing the carrier resin and ethyl acetate to obtain an anti-blue light composite liquid; Step S3: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S4: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0025] Comparative Example 2: See also Figure 1 As shown, this comparative example is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: weigh 15 parts of carrier resin, 2.5 parts of nano-silicon dioxide and 45 parts of ethyl acetate according to weight parts for later use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S2: uniformly mixing the carrier resin, nano-silicon dioxide and ethyl acetate to obtain an anti-blue light composite liquid; Step S3: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S4: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0026] Comparative Example 3: See also Figure 1 As shown, this comparative example is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: Add 2g zinc acetate, 0.04g cadmium chloride, 0.3g lithium hydroxide and 60mL anhydrous ethanol to a three-necked flask equipped with a stirrer and a thermometer, stir and react for 30min at a temperature of 30°C and a stirring rate of 400r / min, then heat to 55°C and continue stirring and reacting for 2h. After the reaction is completed, cool the reaction product to room temperature, pour it into n-hexane, let it stand overnight, and then centrifuge it. Place the precipitate in a vacuum drying oven and dry it at a temperature of 65°C for 2h, then place it in a muffle furnace, calcine it at a temperature of 350°C for 3h, and then cool it with the furnace to obtain a nano anti-blue light agent; Step S2: weigh 15 parts of carrier resin, 2.5 parts of nano anti-blue light agent and 45 parts of ethyl acetate according to weight parts for later use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S3: uniformly mixing the carrier resin, the nano anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step S4: coating the anti-blue light composite liquid on both sides of a PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S5: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0027] Comparative Example 4: See also Figure 1 As shown, this comparative example is a production process of an anti-blue light polarizer, comprising the following steps: Step S1: 25 mmol 2-(tributyltin)thiophene, 0.7 g tetrakis(triphenylphosphine)palladium and 80 mL toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred and reacted for 25 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 10 mmol 2,5-dibromoterephthalate was added and the stirring reaction was continued for 25 min. Then, the mixture was heated to 105° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation. Then, the mixture was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 3 h to obtain intermediate 1. Step S2: 10 mmol of intermediate 1, 25 mmol of N-bromosuccinimide and 70 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas duct, and nitrogen was introduced for protection. The mixture was stirred at 0° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 55° C. and continued to stir for 3 h. After the reaction, the reaction product was cooled to room temperature, and then poured into a saturated sodium thiosulfate solution, and then extracted with dichloromethane for 3 times. The extracts were combined and rotary evaporated to remove the solvent, and then recrystallized with a mixed solvent of ethyl acetate and petroleum ether in a volume ratio of 1:10 to obtain intermediate 2; Step S3: 10 mmol of intermediate 2, 20 mmol of 2,4-dihydroxybenzophenone, 30 mmol of triethylamine and 80 mL of tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 0°C and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 75°C and continued to stir for 6 h. After the reaction, the reaction product was cooled to room temperature, poured into ice water, and then vacuum filtered. The filter cake was washed 3 times with a saturated sodium bicarbonate solution, and then placed in a vacuum drying oven, dried at 55°C for 3 h, and then recrystallized from anhydrous ethanol to obtain intermediate 3; Step S4: 10 mmol of intermediate 3, 50 mmol of sodium hydroxide and 80 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to reflux and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then poured into distilled water, and then extracted with dichloromethane for 3 times, the extracts were combined and rotary evaporated to remove the solvent, to obtain intermediate 4; Step S5: 10 mmol of intermediate 4, 20 mmol of 3-aminopropyltrimethoxysilane, 0.2 g of p-toluenesulfonic acid, 25 mL of toluene and 70 mL of N,N-dimethylacetamide were added to a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then the temperature was raised to reflux and the stirring reaction was continued for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an anti-blue light enhancer; Step S6: 15 parts of carrier resin, 2.5 parts of anti-blue light enhancer and 45 parts of ethyl acetate are weighed in parts by weight for later use; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step S7: uniformly mixing the carrier resin, the anti-blue light enhancer and ethyl acetate to obtain an anti-blue light composite liquid; Step S8: coating the anti-blue light composite liquid on both sides of the PVA film with a thickness of 30 μm, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and compounding a TAC film with a thickness of 80 μm on both sides to obtain a composite base film; Step S9: respectively coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film, wherein the coating thickness of the anti-blue light composite liquid is 15 μm, and the coating thickness of the pressure-sensitive adhesive is 25 μm. Then, a protective film with a thickness of 60 μm is composited on the other side of the anti-blue light composite liquid, and a release film with a thickness of 40 μm is composited on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
[0028] The anti-blue light polarizers prepared in Examples 1-3 and Comparative Examples 1-4 of the present application were irradiated with light of 410 nm wavelength, and the blue light transmittance was measured using a JASCO UV-visible spectrophotometer V-700 to obtain the initial transmittance; After the anti-blue light polarizers prepared in Examples 1-3 and Comparative Examples 1-4 of the present application were continuously irradiated with light of 410 nm wavelength for 30 days, the blue light transmittance was measured using a JASCO UV-visible spectrophotometer V-700 to obtain a continuous transmittance; The test results are shown in the following table:
[0029] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that the anti-blue light polarizer in the present application has excellent anti-blue light performance and can maintain high performance for a long time.
[0030] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0031] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. An anti-blue light polarizer, characterized in that: It is composed of PVA film, anti-blue light composite liquid, TAC film, pressure-sensitive adhesive, protective film and release film; The anti-blue light composite liquid includes the following components in parts by weight: 10-15 parts of carrier resin, 0.5-2.5 parts of composite anti-blue light agent and 40-45 parts of ethyl acetate; Wherein, the composite anti-blue light agent is prepared by the following steps: Step a1: 2-(tributyltin)thiophene, tetrakis(triphenylphosphine)palladium and toluene are stirred for reaction, and then diethyl 2,5-dibromoterephthalate is added and the reaction is continued with stirring. After the reaction is completed, the reaction product is cooled, and then rotary evaporated, washed and dried to obtain intermediate 1; Step a2: stirring the intermediate 1, N-bromosuccinimide and tetrahydrofuran for reaction, cooling the reaction product after the reaction, and then pouring it into a saturated sodium thiosulfate solution, followed by extraction, rotary evaporation of the extract, and then recrystallization to obtain the intermediate 2; Step a3: stirring the intermediate 2, 2,4-dihydroxybenzophenone, triethylamine and tetrahydrofuran for reaction, cooling the reaction product after the reaction, then pouring it into ice water, and then vacuum filtering, washing, drying and recrystallizing the filter cake to obtain the intermediate 3; Step a4: stirring the intermediate 3, sodium hydroxide and anhydrous ethanol to react, cooling the reaction product after the reaction, and then pouring it into distilled water, followed by extraction, and rotary evaporating the extract to obtain the intermediate 4; Step a5: stirring the intermediate 4, 3-aminopropyltrimethoxysilane, p-toluenesulfonic acid, toluene and N,N-dimethylacetamide to react, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain an anti-blue light enhancer; Step a6: stirring zinc acetate, cadmium chloride, lithium hydroxide and anhydrous ethanol for reaction, cooling the reaction product after the reaction is completed, then pouring it into n-hexane, then standing overnight, then centrifuging, drying the precipitate, and then calcining to obtain a nano anti-blue light agent; Step a7: Stir the nano anti-blue light agent, anhydrous ethanol and deionized water to react, then adjust the pH with ammonia water, then add the anti-blue light enhancer and continue stirring the reaction. After the reaction is completed, cool the reaction product, then centrifuge it, wash and dry the precipitate to obtain a composite anti-blue light agent.
2. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the 2-(tributyltin)thiophene, tetrakis(triphenylphosphine)palladium, toluene and diethyl 2,5-dibromoterephthalate in step a1 is 22-25 mmol: 0.3-0.7 g: 70-80 mL: 10 mmol.
3. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the intermediate 1, N-bromosuccinimide and tetrahydrofuran in step a2 is 10 mmol: 22-25 mmol: 60-70 mL.
4. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the intermediate 2, 2,4-dihydroxybenzophenone, triethylamine and tetrahydrofuran in step a3 is 10 mmol: 20 mmol: 25-30 mmol: 60-80 mL.
5. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the intermediate 3, sodium hydroxide and anhydrous ethanol in step a4 is 10 mmol:40-50 mmol:60-80 mL.
6. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the intermediate 4, 3-aminopropyltrimethoxysilane, p-toluenesulfonic acid, toluene and N,N-dimethylacetamide in step a5 is 10 mmol: 20 mmol: 0.1-0.2 g: 20-25 mL: 60-70 mL.
7. The anti-blue light polarizer according to claim 1, characterized in that: The usage ratio of the zinc acetate, cadmium chloride, lithium hydroxide and anhydrous ethanol in step a6 is 2g:0.02-0.04g:0.2-0.3g:50-60mL.
8. The anti-blue light polarizer according to claim 1, characterized in that: The dosage ratio of the nano anti-blue light agent, anhydrous ethanol, deionized water and anti-blue light enhancer in step a7 is 10g:60-70mL:60-70mL:0.7-2.1g; the mass fraction of the ammonia water is 20-25%.
9. A production process for an anti-blue light polarizer, characterized in that: The following steps are involved: Step 1: Weigh 10-15 parts of carrier resin, 0.5-2.5 parts of composite anti-blue light agent and 40-45 parts of ethyl acetate according to weight, and set aside; wherein the carrier resin is Sartomer CN2254NS bifunctional polyester acrylate; Step 2: Evenly mix the carrier resin, the composite anti-blue light agent and ethyl acetate to obtain an anti-blue light composite liquid; Step 3: coating the anti-blue light composite liquid on both sides of the PVA film, and compounding the TAC film on both sides to obtain a composite base film; Step 4: Coat the anti-blue light composite liquid and the pressure-sensitive adhesive on both sides of the composite base film respectively, then composite a protective film on the other side of the anti-blue light composite liquid, and composite a release film on the other side of the pressure-sensitive adhesive to obtain an anti-blue light polarizer.
10. The production process of the anti-blue light polarizer according to claim 9, characterized in that: The thickness of the PVA film is 30-35 μm; the coating thickness of the anti-blue light composite liquid is 15-17 μm; the thickness of the TAC film is 75-80 μm; the coating thickness of the pressure-sensitive adhesive is 25-28 μm; the thickness of the protective film is 58-60 μm; and the thickness of the release film is 38-40 μm.